Rancang Bangun Sistem Informasi Komunitas Motor Rx King di Kudus Berbasis Web - Umam, Khothibul; Endang Supriyati; Tri Listyorini (Yayasan Literasi Sains Indonesia, 2023)
The RX King community is a forum for classic motorbike lovers with various models and modifications. Within the group, messages are exchanged and the message exchange is carried out through group communication. However, community members still need a system to interact, discuss and search for information in one place. One of the RX King communities is in the city of Kudus. The problems that occurred were raised in this research. This research has the benefit of providing a forum for administrators and members of the RX King motorbike community in Kudus to interact so that a website-based information system for the RX King motorbike community in Kudus is developed. The data collection methods used in this research were interviews with the head of the RX King Kudus community, direct observation at the base camp and documentation. This system was created using the CodeIgniter framework and the waterfall research method. This waterfall method includes requirements, design, implementation, testing. The results of this research are an information system for the RX King community in Kudus city.